The Optimizing The Role Of Advisors in Supporting the Academic Achievement of Management Students Through a Structured Guidance Program - Nirwana, Baiq Nadia; Marswandi, Ega Dwi Putri; Talidobel, Susilo; Wardi, Putri Amalia; Hakiki, M. Indrawan (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2025)
The role of academic advisors in higher education becomes the frontline in guiding students not only in academic aspects but also in psychological aspects. However, academic performance is still often viewed as merely an administrative activity, so its potential to enhance student performance has not been fully realized. The purpose of this service is to develop and implement a structured academic program that can methodically calculate academic advisors. Activities were carried out through training for academic advisors, evaluation of the advising module, and evaluation of program effectiveness. The results show a significant improvement in the quality of interaction between students, the effectiveness of academic support, and student loyalty. This article highlights the importance of institutional support for structured mentoring as a component of the higher education quality system